Composite polymer electrolyte membrane and preparation method and application thereof

By modifying the surface of an inorganic solid electrolyte with barium titanate and combining it with polymer materials, a composite polymer electrolyte membrane was prepared, which solved the safety and cycle life problems of lithium-ion batteries and achieved efficient ion conduction and improved battery performance.

CN120914322APending Publication Date: 2025-11-07SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511069278.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-11-07

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have liquid electrolytes that are flammable and explosive, have narrow electrochemical windows, and have high contact resistance at the interface between solid electrolytes and electrodes, resulting in insufficient battery safety and cycle life.

Method used

A composite polymer electrolyte membrane is used. By modifying the surface of the inorganic solid electrolyte with barium titanate, its piezoelectric properties are used to regulate the ion transport path and electric field distribution. Combined with a flexible polymer material, a polarization field is formed to balance the internal stress and electric field of the battery, suppressing thermal runaway and interfacial impedance.

Benefits of technology

It significantly improves the ion conduction efficiency and charge/discharge performance of lithium-ion batteries, enhances battery safety and cycle stability, and reduces usage risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120914322A_ABST
    Figure CN120914322A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion solid-state batteries, and relates to a composite polymer electrolyte membrane as well as a preparation method and application thereof. The preparation method of the composite polymer electrolyte membrane comprises the following steps: generating a precursor salt containing Ba and Ti on the surface of an inorganic solid electrolyte through a wet chemical method, and forming a compact barium titanate coating layer on the surface of the electrolyte in a high-temperature calcination process to obtain the barium titanate surface modified inorganic solid electrolyte; uniformly dissolving a high-molecular polymer material, the barium titanate surface modified inorganic solid electrolyte and a lithium salt in a solvent, heating and stirring to prepare a uniform solution; and drying to form a membrane to obtain the polymer composite electrolyte membrane. Barium titanate has a special piezoelectric property and can be spontaneously polarized in a crystal structure to generate a polarization field, and the polarization field can sensitively sense the nonuniformity of lithium ion transmission dynamics and interact with the nonuniformity to balance the transmission process of lithium ions in the solid electrolyte, so that the bottleneck problem of ion migration in the traditional electrolyte is solved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of lithium ion solid-state batteries, and particularly relates to a composite polymer electrolyte film and a preparation method and application thereof. BACKGROUND

[0002] As the mainstream energy storage technology, the performance of the core component electrolyte of lithium ion batteries directly determines the safety and cycle life of the batteries. Currently, commercial lithium ion batteries mostly use liquid organic electrolytes, but they contain flammable carbonate solvents (such as EC, DEC), which are extremely easy to cause thermal runaway and even explosion when overcharged, short-circuited or mechanically damaged, seriously threatening user safety. In addition, the electrochemical window of the liquid electrolyte is narrow (<4.5 V), which is difficult to match high-voltage cathode materials (such as LiNi 0.8 Mn 0.1 Co 0.1 O2), limiting the further improvement of energy density.

[0003] Solid-state electrolytes are considered as the ideal choice for the next generation of batteries due to their non-flammability and wide electrochemical window. Among them, polymer-based solid-state electrolytes (such as PVDF, PEO) are highly concerned due to their good flexibility, easy processing and other advantages, but their room temperature ionic conductivity is about 10 -5 S·cm -1 , and the interface contact impedance with the electrode is high, resulting in insufficient rate performance and cycle stability of the battery. Oxide solid-state electrolytes (such as LATP, LLZO) have high ionic conductivity (10 -4 ~10 -3 S·cm -1 ), but their rigid structure is easy to form point contact with the electrode, and is easy to have interface side reactions with lithium metal (such as Ti 4+ in LATP is reduced to Ti 3+ ) in the cycle, resulting in blockage of ion transport channels and sharp increase of interface impedance, especially the uneven kinetics of ion transport between the positive and negative electrodes leads to the decline of electrochemical performance.

[0004] Regulating the composition and structure of each interface layer in the lithium ion solid-state battery to improve the ionic conductivity and ion transport kinetics at the interface has become a major research topic. Ion transport is mainly affected by the number of carriers, concentration gradient and electric field distribution in the interface region. Dielectrics with piezoelectric or ferroelectric effect can actively adapt to and adjust the uneven stress and electric field changes at the multiphase interface in the ion transport process. SUMMARY

[0005] The application aims to provide a composite polymer electrolyte membrane and a preparation method and application thereof, solve the bottleneck problem of ion migration in a traditional electrolyte, cooperate with LATP to strengthen ion conduction, greatly improve ion conduction efficiency, and significantly improve battery charging and discharging performance.

[0006] In order to achieve the above-mentioned purpose, the application adopts the following technical scheme: The application discloses a preparation method of a composite polymer electrolyte membrane, comprising the following steps: S1, ultrasonic dispersion of inorganic solid electrolyte powder in a mixed solution of deionized water and anhydrous ethanol to form a suspension; Barium acetate, tetrabutyl titanate and a template agent are dissolved in deionized water to form a colorless transparent barium titanate precursor solution; S2, the colorless transparent barium titanate precursor solution is added to the suspension, and continuous stirring is performed to obtain a uniform coating liquid, and aging is performed; S3, the aged coating liquid is subjected to centrifugal treatment to obtain a solid powder; The solid powder is subjected to heat treatment at 600-700 DEG C under an oxygen atmosphere, and the holding time is 2-6 h; and after cooling, the inorganic solid electrolyte after surface modification of barium titanate is obtained; S4, under the protection of an inert gas, a polymer material, the inorganic solid electrolyte after surface modification of barium titanate and lithium salt are uniformly dissolved in a solvent, and stirring is performed at 50-80 DEG C for 1-2 h to prepare a uniform solution; The uniform solution is dried into a film to obtain a polymer composite electrolyte membrane.

[0007] Further, in S1, the inorganic solid electrolyte is any one or any combination of Li7La3Zr2O 12 , Li 0.5 La 0.5 TiO3, Li 1.4 Al 0.4 Ti 1.6 (PO4)3.

[0008] Further, in S1, the template agent is polyethylene glycol, hexamethylenetetramine, citric acid, urea, polyvinylpyrrolidone or cetyltrimethylammonium bromide.

[0009] Further, in the inorganic solid electrolyte after surface modification of barium titanate, the barium titanate accounts for (2-10) % of the mass of the inorganic solid electrolyte.

[0010] Further, in S2, continuous stirring is performed for 4-8 h, and aging is performed for 6-24 h.

[0011] Further, in S4, the high polymer material is any one or a combination of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polypropylene oxide (PPO), polyvinylidene chloride (PVDC), polyethylene carbonate (PEC), polytrimethylene carbonate (PTMC), polypropylene carbonate (PPC), and derivatives thereof.

[0012] Further, in S4, the lithium salt is any one or a combination of LiClO4, LiTFSI, LiBOB, and LiNO3.

[0013] Further, in S4, the mass ratio of the high polymer material, the inorganic solid-state electrolyte after surface modification of barium titanate, and the lithium salt is (2-6.5):(2-4):(2-5.5).

[0014] The application further discloses a composite polymer electrolyte film prepared by the preparation method.

[0015] The application further discloses application of the composite polymer electrolyte film in preparation of a battery, wherein the discharge specific capacity is greater than 190 mAh g -1 at a current density of 0.1 C, and the discharge specific capacity reaches 180 mAh g -1 at a large current density of 1 C.

[0016] Compared with the prior art, the application has the following beneficial technical effects: The application discloses a preparation method of a composite polymer electrolyte film, which comprises the following steps: first, preparing an inorganic solid-state electrolyte after surface modification of barium titanate; and then, mixing a high polymer material, the inorganic solid-state electrolyte after surface modification of barium titanate, and a lithium salt to prepare a film. Barium titanate is added because barium titanate has special piezoelectric properties, can spontaneously polarize in a crystal structure, and can generate a polarization field. The polarization field can sensitively perceive the inhomogeneity of lithium ion transmission dynamics, interact with the inhomogeneity, and balance the transmission process of lithium ions in the solid-state electrolyte. By optimizing the ion transmission path, the bottleneck problem of ion migration in a traditional electrolyte is solved, and the ion conduction efficiency is greatly improved by strengthening ion conduction of the inorganic solid-state electrolyte powder, so that the charge and discharge performance of the battery is significantly improved.

[0017] Oxide solid-state electrolytes such as LLZO are too rigid and fragile, and are difficult to stably work under high-rate charge and discharge. In the application, a high polymer material with better flexibility is used as a matrix, and barium titanate is uniformly dispersed in the matrix during the preparation process. The polarization field generated by spontaneous polarization of barium titanate not only adjusts ion transmission, but also has an impact on intermolecular forces, so that the flexibility of the overall structure is improved. This makes the battery better adapt to various deformations and stresses in different use environments. The organic liquid and gel electrolyte used in commercial lithium-ion batteries has safety hazards such as volatility, flammability and explosion. The coating film of the present application has unique composition and preparation process. The polarization field formed by the spontaneous polarization of barium titanate builds a dynamic balance mechanism inside the battery. When encountering extreme conditions such as high temperature, short circuit and puncture, the polarization field can adjust the electric field distribution inside the battery, inhibit the dangerous reactions that may cause thermal runaway, and make the coating film not easy to burn and explode, greatly reducing the risk of battery use.

[0018] The existing solid-state electrolyte has poor compatibility with the electrode material, resulting in increased interface impedance and reduced battery cycle performance. In the present application, the polarization field of the barium titanate coating layer plays a key role. When in contact with the positive and negative electrode materials, the polarization field can actively adjust the ion transport at the interface, balance the unevenness of ion transport kinetics, effectively reduce the interface impedance, and promote smooth charge transport. This not only improves the battery charge and discharge efficiency, but also enhances the cycle stability, allowing the battery to maintain high capacity retention rate and stable performance after multiple charge and discharge cycles. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 A photo of the composite solid-state electrolyte film prepared in the present application; Figure 2 XRD patterns of three kinds of composite solid-state electrolyte films prepared in Examples 1-3 of the present application; Figure 3 Cycle performance graph of the composite solid-state electrolyte film prepared in Examples 1-3 of the present application; Figure 4 CV graph of the battery after assembling the three kinds of composite electrolyte films prepared in Examples 1-3 of the present application. DETAILED DESCRIPTION

[0020] The present application is further illustrated in conjunction with the drawings and specific embodiments.

[0021] In view of the side reactions that occur when inorganic solid-state electrolyte materials come into contact with lithium metal, leading to poor cycle and rate performance, the piezoelectric material barium titanate (BaTiO3) can generate an internal built-in polarization field under an applied electric field or mechanical stress due to its unique piezoelectric effect and spontaneous polarization characteristics. Theoretically, it can direct the migration of lithium ions, while its high dielectric constant (ε>1000) can weaken the coupling between lithium ions and polymer chains, improving ion mobility. In addition, barium titanate can prevent direct contact between inorganic solid-state electrolyte and lithium metal, stabilize the interface, balance the electric field inside the battery, and inhibit the accumulation of electrons, thereby inhibiting the growth of lithium metal dendrites.

[0022] Example 1 The present application discloses a preparation method of a composite polymer electrolyte film, comprising the following steps: (1) LATP is ultrasonically dispersed in a mixed solution of deionized water and anhydrous ethanol to form a white suspension liquid.

[0023] (2) Barium acetate, tetrabutyl titanate and polyethylene glycol are respectively dissolved in deionized water to form a colorless transparent barium titanate precursor solution.

[0024] (3) The colorless transparent barium titanate precursor solution containing metal salt and template agent is added dropwise into the white suspension liquid obtained in step (1), and the oil bath is continuously stirred for 4 h to obtain a uniform coating liquid, and the coating liquid is aged for 12 h.

[0025] (4) The coating liquid obtained in step (3) is centrifuged, and the collected solid powder is heat treated in an oxygen atmosphere at a temperature of 650 DEG C for 3 h, and then naturally cooled to obtain LATP with a barium titanate surface modification, wherein the barium titanate is 2% of the mass of the inorganic solid electrolyte; marked as 2%BTO@LATP.

[0026] (5) Under the protection of inert gas, PVDF, 2%BTO@LATP and LiTFSI are uniformly dissolved in N,N-dimethylformamide (DMF) at a mass ratio of 5:3:2, and stirred at a constant temperature of 55 DEG C for 2 h to prepare a uniform solution; (6) Under the protection of inert gas, the uniform solution is slowly poured into a mold and sealed, and placed in a vacuum drying box and dried at 60 DEG C for 48 h to obtain a composite polymer electrolyte membrane, marked as PVDF-LATP-BTO-1.

[0027] Example 2 The application discloses a preparation method of a composite polymer electrolyte membrane. (1) LATP is ultrasonically dispersed in a mixed solution of deionized water and anhydrous ethanol to form a white suspension liquid.

[0028] (2) Barium acetate, tetrabutyl titanate and 6 wt% polyethylene glycol are respectively dissolved in deionized water to form a colorless transparent barium titanate precursor solution.

[0029] (3) The colorless transparent barium titanate precursor solution containing metal salt and template agent is added dropwise into the suspension liquid containing LATP, and the oil bath is continuously stirred for 4 h to obtain a uniform coating liquid, and the coating liquid is aged for 12 h.

[0030] (4) The above obtained solution is centrifuged, and the collected solid powder is heat treated in an oxygen atmosphere at a temperature of 650 DEG C for 3 h, and then naturally cooled to obtain LATP with a barium titanate surface modification, wherein the barium titanate is 4% of the mass of the inorganic solid electrolyte; the sample is marked as 4%BTO@LATP.

[0031] (5) Under the protection of inert gas, PVDF, 4% BTO@LATP and LiTFSI were uniformly dissolved in N, N-dimethylformamide (DMF) at a mass ratio of 5:3:2, stirred at 55°C for 2 h, and prepared into a uniform solution; (6) Under the protection of inert gas, the solution was slowly poured into a mold for molding, and was sealed and placed in a vacuum drying oven at 60°C for 48 h to obtain a composite polymer electrolyte membrane, which was marked as PVDF-LATP-BTO-2.

[0032] Example 3 The application discloses a preparation method of a composite polymer electrolyte membrane. (1) LATP was ultrasonically dispersed in a mixed solution of deionized water and anhydrous ethanol to form a white suspension liquid.

[0033] (2) Barium titanate was prepared by dissolving barium acetate, tetrabutyl titanate and 6 wt% polyethylene glycol in deionized water at a mass ratio of 6 wt% to form a colorless transparent barium titanate precursor solution.

[0034] (3) The colorless transparent barium titanate precursor solution containing metal salt and template agent was added dropwise into the suspension liquid containing LATP, and oil bath continuous stirring was performed for 4 h to obtain a uniform coating solution, and aging was performed for 12 h.

[0035] (4) The obtained solution was subjected to centrifugal treatment, and the collected solid powder was subjected to heat treatment in an oxygen atmosphere at a heat treatment temperature of 650°C for 3 h, and after natural cooling, the LATP modified by barium titanate was obtained, wherein the barium titanate is 2% of the mass of the inorganic solid-state electrolyte; the sample is marked as 6%BTO@LATP.

[0036] (5) Under the protection of inert gas, PVDF, 6%BTO@LATP and LiTFSI were uniformly dissolved in N, N-dimethylformamide (DMF) at a mass ratio of 5:3:2, stirred at 55°C for 2 h, and prepared into a uniform solution; (6) Under the protection of inert gas, the solution was slowly poured into a mold for molding, and was sealed and placed in a vacuum drying oven at 60°C for 48 h to obtain a composite polymer electrolyte membrane, which was marked as PVDF-LATP-BTO-3.

[0037] Example 4 The difference between the example 1 and the example 4 is that the LATP modified by barium titanate prepared in step (4) is 10% of the mass of the inorganic solid-state electrolyte, which is marked as 10%BTO@LATP.

[0038] Example 5 A method for preparing a composite polymer electrolyte membrane is disclosed, comprising the following steps: (1) Ultrasonic dispersion of LLZO in a mixed solution of deionized water and anhydrous ethanol to form a white suspension liquid.

[0039] (2) Dissolve barium acetate, tetrabutyl titanate and 6 wt% hexamethylene tetramine in deionized water respectively to form a colorless transparent barium titanate precursor solution.

[0040] (3) Add the colorless transparent barium titanate precursor solution containing metal salt and hexamethylene tetramine dropwise to the suspension liquid containing LLZO, continuously stir in an oil bath for 4 h, obtain a uniform coating liquid, and age for 12 h.

[0041] (4) Centrifugal treatment of the above obtained solution, heat treatment of the collected solid powder in oxygen atmosphere, heat treatment temperature is 600 ℃, time is 3 h, after natural cooling, obtain LLZO with surface modification of barium titanate, wherein the barium titanate is 2% of the mass of LLZO electrolyte; marked as 2%BTO@LLZO.

[0042] (5) Under the protection of inert gas, uniformly dissolve PEO, 2%BTO@LLZO and LiClO4 in N,N-dimethylformamide (DMF) with a mass ratio of 5:3:2, stir for 2 h at 55 ℃, prepare a uniform solution; (6) Under the protection of inert gas, slowly pour the solution into the mold, seal it, and place it in a vacuum drying oven at 60 ℃ for 48 h, obtain the composite polymer electrolyte membrane.

[0043] Example 6 A method for preparing a composite polymer electrolyte membrane is disclosed, comprising the following steps: (1) Ultrasonic dispersion of LLTO in a mixed solution of deionized water and anhydrous ethanol to form a white suspension liquid.

[0044] (2) Dissolve barium acetate, tetrabutyl titanate and hexamethylene tetramine in deionized water respectively to form a colorless transparent barium titanate precursor solution.

[0045] (3) Add the colorless transparent barium titanate precursor solution containing metal salt and hexamethylene tetramine dropwise to the suspension liquid containing LLZO, continuously stir in an oil bath for 4 h, obtain a uniform coating liquid, and age for 12 h.

[0046] (4) The obtained solution is subjected to centrifugal treatment, and the collected solid powder is subjected to heat treatment under an oxygen atmosphere at a temperature of 600 DEG C for 6 h, and after natural cooling, a surface-modified LLTO of barium titanate is obtained, wherein the barium titanate is 2% of the mass of the LLZO electrolyte; marked as 2%BTO@LLTO.

[0047] (5) Under the protection of inert gas, polyacrylic acid methyl ester PMMA, 2%BTO@LLTO and LiBOB are uniformly dissolved in N,N-dimethylformamide (DMF) at a mass ratio of 2:4:3, stirred for 2 h at a constant temperature of 55 DEG C, and a uniform solution is prepared; (6) Under the protection of inert gas, the solution is slowly poured into a mold for molding, and the mold is sealed and placed in a vacuum drying box for drying at 60 DEG C for 48 h, and a composite polymer electrolyte membrane is obtained.

[0048] Example 7 The application discloses a preparation method of a composite polymer electrolyte membrane. (1) LLTO is ultrasonically dispersed in a mixed solution of deionized water and anhydrous ethanol to form a white suspension liquid.

[0049] (2) Barium acetate, tetrabutyl titanate and hexamethylenetetramine are respectively dissolved in deionized water to form a colorless transparent barium titanate precursor solution.

[0050] (3) The colorless transparent barium titanate precursor solution containing metal salt and hexamethylenetetramine is added dropwise into the suspension liquid containing LLZO, oil bath continuous stirring is carried out for 8 h, a uniform coating liquid is obtained, and aging is carried out for 24 h.

[0051] (4) The obtained solution is subjected to centrifugal treatment, and the collected solid powder is subjected to heat treatment under an oxygen atmosphere at a temperature of 700 DEG C for 2 h, and after natural cooling, a surface-modified LLTO of barium titanate is obtained, wherein the barium titanate is 2% of the mass of the LLZO electrolyte; marked as 2%BTO@LLTO.

[0052] (5) Under the protection of inert gas, polyacrylic acid methyl ester PMMA, 2%BTO@LLTO and LiBOB are uniformly dissolved in N,N-dimethylformamide (DMF) at a mass ratio of 2:4:3, stirred for 2 h at a constant temperature of 55 DEG C, and a uniform solution is prepared; (6) Under the protection of inert gas, the solution is slowly poured into a mold for molding, and the mold is sealed and placed in a vacuum drying box for drying at 60 DEG C for 48 h, and a composite polymer electrolyte membrane is obtained.

[0053] As Figure 1The image shows a photograph of the composite solid electrolyte membrane PVDF-LATP-BTO-2 prepared according to an embodiment of the present invention. As can be seen from the image, the electrolyte membrane is relatively smooth, which promotes uniform transport of lithium ions.

[0054] like Figure 2 As shown, the XRD patterns obtained by diffraction analysis of the three composite solid electrolyte membranes prepared in Examples 1-3 of this invention show that the introduction of LATP and BTO weakens the crystallization peak of PVDF, effectively inhibits the ordered arrangement of the polymer, and promotes amorphization. This helps to improve lithium-ion conductivity.

[0055] like Figure 3 As shown, the three composite solid electrolyte membranes prepared in Examples 1-3 of this invention were used to make batteries, and the cycle performance was analyzed, resulting in cycle performance graphs. From Figure 3 As can be seen, PVDF-LATP-BTO-2 has the highest specific capacity and almost no decay during cycling, exhibiting the best cycling performance.

[0056] like Figure 4 The figure shows the CV curves of the three composite electrolyte membranes after they were assembled into batteries. It can be seen that the battery has low polarization and low interfacial charge transfer resistance.

[0057] When the three composite electrolyte membranes prepared in Examples 4-7 of this invention were analyzed for cycling performance, they showed almost no degradation during cycling and excellent cycling performance; the battery polarization was small and the interfacial charge transfer resistance was low.

[0058] Barium titanate, as a piezoelectric material, can adapt to and regulate the non-uniform stress changes at the multiphase interface during ion transport, ensuring the stability of lithium insertion / extraction and improving the interfacial compatibility. Moreover, it can effectively suppress the side reactions between inorganic electrolyte and lithium, reduce electrolyte degradation, lower low interfacial impedance, and improve the cycle stability of solid-state batteries.

Claims

1. A method for producing a composite polymer electrolyte membrane, characterized by, The preparation method comprises the following steps: S1, dispersing inorganic solid electrolyte powder in a mixed solution of deionized water and anhydrous ethanol by ultrasonic to form a suspension; S2, adding the colorless transparent barium titanate precursor solution into the suspension and continuously stirring to obtain a uniform coating liquid and aging; S3, centrifuging the aged coating liquid to obtain a solid powder; S4, dissolving a high polymer material, the inorganic solid electrolyte after surface modification of barium titanate and lithium salt in a solvent under the protection of inert gas, stirring at 50-80 ℃ for 1-2 h to prepare a uniform solution; S5, drying the uniform solution into a film to obtain a polymer composite electrolyte film. In S1, the template agent is polyethylene glycol, hexamethylene tetramine, citric acid, urea, polyvinyl pyrrolidone or bromide hexadecyl trimethyl ammonium. In the inorganic solid electrolyte after surface modification of barium titanate, the mass fraction of barium titanate in the inorganic solid electrolyte is (2-10) %.

2. The method of claim 1, wherein the composite polymer electrolyte membrane is prepared by the steps of: In S1, the inorganic solid-state electrolyte is any one or a combination of Li7La3Zr2O 12 , Li 0.5 La 0.5 TiO3, Li 1.4 Al 0.4 Ti 1.6 (PO4)3.

3. The method for preparing a composite polymer electrolyte membrane according to claim 1, characterized in that, In S2, continuously stirring for 4-8 h and aging for 6-24 h.

4. The method for preparing a composite polymer electrolyte membrane according to claim 1, characterized in that, In S4, the high polymer material is any one or combination of polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polypropylene oxide (PPO), polyvinylidene chloride (PVDC), polyethylene carbonate (PEC), polytrimethylene carbonate (PTMC), polypropylene carbonate (PPC) and derivatives thereof.

5. The method for preparing a composite polymer electrolyte membrane according to claim 1, characterized in that, In S4, the lithium salt is any one or combination of LiClO4, LiTFSI, LiBOB and LiNO3.

6. The method for preparing a composite polymer electrolyte membrane according to claim 1, characterized in that, In S4, the mass ratio of the high polymer material, the inorganic solid electrolyte after surface modification of barium titanate and lithium salt is (2-6.5):(2-4):(2-5.5).

7. The method for preparing a composite polymer electrolyte membrane according to claim 1, characterized in that, 9. A composite polymer electrolyte film prepared by the preparation method of any one of claims 1-8.

8. The method for preparing a composite polymer electrolyte membrane according to claim 1, characterized in that, ​ ​ 10. Use of a composite polymer electrolyte membrane according to claim 9 for the preparation of a battery, characterized in that, Discharge specific capacity > 190 mAh g at a current density of 0.1 C -1 Discharge specific capacity of 180 mAh g at a high current density of 1 C -1 .

Citation Information

Cited By

  • Copper-based island catalyst synergistically modified by MTW-MFI eutectic molecular sieve and CeO2 as well as preparation method and application of copper-based island catalyst

    CN122057559A

  • F127 and ionic liquid synergistically modified composite solid electrolyte, electrolyte membrane, preparation method and application

    CN122091734A